2016
DOI: 10.4172/2157-7587.1000236
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration in 15 Tree Species Grown on a Phytocapped Landfill Site

Abstract: An alternative landfill capping technique 'Phytocapping' (establishing plants on a layer of soil placed over the waste) was trialled at Rockhampton, Australia. In this capping trees act as 'bio-pumps and 'rain interceptors' and soil cover as 'storage'. They together minimise water percolation leading to reduced leachate production. "Transpiration" is a vital process to maintain the hydrological balance of a particular site. To be successful, the trees must transpire enough water from the soil so as to reduce w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…A natural extension of this research will be incorporating this species-specific SA-DBH allometric data to estimate stand-level transpiration (Granier 1987;Meinzer et al 2001;James et al 2002;Ford et al 2004;Oishi et al 2008). The analysis of species contribution to total stand transpiration is an emergent topic (Gebre et al 1998;Ewers et al 2002;Kostner et al 2002;Pataki et al 2005;Hernandez-Santana et al 2015;Venkatraman and Ashwath 2016). A recent study across Alaska and western Canadian boreal forests found significant differences among deciduous and conifer tree species in their capacity to take up snowmelt water (Young-Robertson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A natural extension of this research will be incorporating this species-specific SA-DBH allometric data to estimate stand-level transpiration (Granier 1987;Meinzer et al 2001;James et al 2002;Ford et al 2004;Oishi et al 2008). The analysis of species contribution to total stand transpiration is an emergent topic (Gebre et al 1998;Ewers et al 2002;Kostner et al 2002;Pataki et al 2005;Hernandez-Santana et al 2015;Venkatraman and Ashwath 2016). A recent study across Alaska and western Canadian boreal forests found significant differences among deciduous and conifer tree species in their capacity to take up snowmelt water (Young-Robertson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Urban street trees are normally medium/large size trees planted in small areas of bare and permeable soil: for this reason, the soil water evaporation is generally less than plant transpiration. We can therefore assume that evapotranspiration losses can be included in a single function that depends on soil moisture and plant species through a reference transpiration rate T r and an indication of plant water stress s * (Cregg 1995;Nouri et al 2013;Venkatraman and Ashwath 2016). A piecewise linear function is used to this purpose (see Eq.…”
Section: Soil Moisture Dynamicsmentioning
confidence: 99%
“…Celle-ci est fonction, d'une part, du diamètre et de la densité des vaisseaux du xylème (Tateishi et al, 2008) part, du rapport entre la surface foliaire et celle de l'aubier (West et al, 1999 ;. La résistance hydraulique existant entre le sol et la canopée peut également avoir une influence car elle varie en fonction de la hauteur de l'arbre et de la perméabilité de l'aubier (Venkatraman et Ashwath, 2016). Enfin, l'état sanitaire et la vigueur des arbres, en lien avec leur âge plus ou moins avancé, peuvent influencer l'état des vaisseaux, et donc la transpiration.…”
Section: La Densité De Flux De Sèveunclassified